2016
DOI: 10.1631/jzus.b1500321
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-enhancing effects of hydrolysate of polygalasaponin in SAMP8 mice

Abstract: Abstract:Objectives: The aim of the study is to evaluate the cognitive-enhancing effects of hydrolysate of polygalasaponin (HPS) on senescence accelerate mouse P8 (SAMP8) mice, an effective Alzheimer's disease (AD) model, and to research the relevant mechanisms. Methods: The cognitive-enhancing effects of HPS on SAMP8 mice were assessed using Morris water maze (MWM) and step-through passive avoidance tests. Then N-methyl-D-aspartate (NMDA) receptor subunit expression for both the cortex and hippocampus of mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
(60 reference statements)
1
10
0
Order By: Relevance
“…These findings are in line with other studies showing that SAMP8 mice displayed a significant increase in escape latency time since the first day of training as compared with SAMR1 mice, while no significant difference was observed among training days [38, 39].…”
Section: Resultssupporting
confidence: 92%
“…These findings are in line with other studies showing that SAMP8 mice displayed a significant increase in escape latency time since the first day of training as compared with SAMR1 mice, while no significant difference was observed among training days [38, 39].…”
Section: Resultssupporting
confidence: 92%
“…Aberrations in the lower symmetrical regions in the DMN (such as the precuneus and fusiform) could be the principal reason for memory decline. These regions play an important role in visual information processing of AD patients (Chang et al, 2015;Xu et al, 2016). Buckner et al (2005) also observed that disruption of the medial temporal lobe contributed to memory impairment.…”
Section: Fig 2 Analysis Of Vmhc Resultsmentioning
confidence: 93%
“…Besides, the content of phosphorylated and non-phosphorylated NMDAR subunits in the hippocampus of AD patients are reduced (Sze et al, 2001). Consistently, in SAMP8 mice or AD models injected with Aβ 25-35 or Aβ 1-42 , the expression of NMDAR1, NMDAR2A and NMDAR2B were decreased markedly in the hippocampus or cortex (K. W. Chang et al, 2020; K. Wang et al, 2018; Xu et al, 2016). Moreover, it has been demonstrated that ketamine, a noncompetitive NMDAR antagonist, could ameliorate the impaired learning and memory of developing mice induced by repetitive mechanical stress, and the mechanism may be associated with the increased hippocampal BDNF expression (C. H. Chang, Su, & Gean, 2018; Peng, Zhang, Wang, Ren, & Zhang, 2011).…”
Section: Discussionmentioning
confidence: 67%